Civil law enforcement of the rights of the patients with mental disorders: Ukrainian legislation and international practice - Shutak, Illya D.; Koroied, Sergii O.; Kovalskyy, Mykhaylo M.; Makhinchuk, Vitalii M.; Briukhovetska, Maryna S. (Cuestiones Políticas, 2020)
There is a need to determine the patient's condition in the process of establishing legal relationships with the medical institution, as well as guaranteeing their human rights. The issue of guaranteeing the rights of patients with mental disorders has become particularly acute, which has led to the relevance of this study. For this reason, the objective of the article is to determine the status of the patient with mental disorder in civil law relationships, between him and the medical institution by examining the respective legal literature, the jurisprudence of the European Court of Human Rights and the Acts. national and international legal. In the course of the study the following methods were used: dialectical, structural and systemic, analytical and synthetic, analytical and synthetic, comparative and legal, formal and legal, sociological. The study found that reform of existing legislation has led to a new regulatory policy in the area of healthcare. There are no specific rules in civil law that determine the status of the patient with a mental disorder, as well as the possibilities and methods of protection of their rights. Furthermore, mental health services, given their details, need to be further regulated at the legislative level.